Diagnostics of atypical pulmonary infections - Adamczyk, Patryk; Parkolap, Julia; Kiryszewska-Jesionek, Agnieszka; Pastuszak-Lewandoska, Dorota (Medical Studies/Studia Medyczne, 2023)
Atypical community-acquired pneumonia (CAP) is a lung infection caused by atypical bacteria. It is associated with non-specific symptoms, the course of the disease is unusual and it poses a serious threat to patients. Even though CAP is quite prevalent, most cases remain undiagnosed, and clinicians rely solely on empirical therapy. The aim of this article is to characterize the most frequently used methods in diagnostics of atypical CAPs and evaluate their efficacy. A literature review showed that most of these techniques are still under development and there is a need for standardized diagnostic algorithms for atypical infections. Molecular panels and serological assays have been especially emphasized as they allow for rapid identification of etiologic agents and antibiotic resistance.